Assessing the impact of U.S. economic aid and military support on the strategic dynamics of Pakistan’s foreign policy: a study of diplomatic relations and public sentiment - Hafsa Gul; Imran Naseem; Muhammad Bahar Khan; Khalid Zaman (Future Business Journal)
Abstract The study utilizes a mixed-methods approach to address a gap in the existing literature by investigating the impact of U.S. economic assistance, shifts in U.S. military backing, diplomatic disagreements, and public opinion on Pakistan’s foreign policy decisions. Previously, there was a focus on isolated aspects of this relationship, such as economic or military factors. The regression results indicate that U.S. economic aid (− 0.46, p < 0.001) and diplomatic disputes (− 0.31, p < 0.025) have a negative impact on Pakistan’s foreign policy decision-making, whereas changes in U.S. military support (0.25, p < 0.013) positively influence it. The results imply a negative impact of U.S. economic aid, indicating that Pakistan’s policy autonomy is limited due to increased economic dependence. On the other hand, modifications to U.S. military assistance demonstrate a noteworthy positive impact, indicating that increased military collaboration supports assertive policy initiatives. Qualitative results show that Pakistan views the alignment with the U.S. as a way to get financial, military, and diplomatic support from the U.S., enhancing its influence and strategic position in the area. Financial considerations, such as maintaining trade advantages and receiving financial backing from the U.S., influence Pakistan’s decisions about its foreign policy. Pakistan would have to reassess its strategic priorities if U.S. economic aid was cut back or modified. Conditionality allows the United States to achieve certain policy objectives, like counterterrorism cooperation, human rights reforms, and regional stability, by linking aid to desired outcomes. The validity of dependency theory and military support’s effect on asymmetric coalitions illuminate bilateral power dynamics. The research suggests bilateral frameworks, varied economic partnerships, and increased military cooperation to decrease dependency and boost policy autonomy. The findings illustrate aid-politics dynamics by integrating quantitative and qualitative data and contributing to foreign policy analysis literature.